Hall and Joule’s heating Influences on Peristaltic Transport of Bingham plastic Fluid with Variable Viscosity in an Inclined Tapered Asymmetric Channel - Yousif Hassen, Rasha; A. Ali, Hayat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
This paper presents an investigation of peristaltic flow of Bingham plastic fluid in an inclined tapered asymmetric channel with variable viscosity. Taken into consideration Hall current, velocity, thermal slip conditions, Energy equation is modeled by taking Joule heating effect into consideration and by holding assumption of long wavelength and low Reynolds number approximation these equations simplified into couple of non-linear ordinary differential equations that solved using perturbation technique. Graphical analysis has been involved for various flow parameters emerging in the problem. We observed two opposite behaviors for Hall parameter and Hartman number on velocity axial and temperature curves.